Impact of food-based fortification on nutritional outcomes and acceptability in older adults: systematic literature review - Geny, Alexia; Petitjean, Maité; Van Wymelbeke-Delannoy, Virginie; Sulmont-Rossé, Claire (Frontiers in Nutrition, 2023)
Background. "Do it yourself" (DIY) food-based fortification involves adding fortificants into everyday foods. It is a flexible solution that allows older people with reduced appetite to meet their nutritional needs. Objectives. The aims of the systematic review are (a) to describe DIY fortified recipes, (b) to evaluate their acceptability, and (c) to evaluate whether they are effective levers to improve nutritional outcomes in older people. Methods. A systematic search of 3 databases (Web of Science, Pubmed, Scopus, last searched on January 2022) was undertaken. Main eligibility criteria include older adults aged ≥ 60 years living at home, in an institution or in hospital. Studies carried out for a specific medical condition or targeting only micronutrient fortification were excluded. After reviewing all titles/abstracts then full-text papers, key data were extracted and synthesized narratively. The quality of included studies was assessed using Kmet et al. (2004). Results. Of 21 493 papers extracted, 44 original studies were included (3 384 participants), with 31 reporting nutritional outcomes, 3 reporting acceptability outcomes and 10 reporting both nutritional and acceptability outcomes. The review highlighted a wide variety of DIY fortified recipes, with additional energy ranging from 23 to 850 kcal/d (M=403; SE=62) and/or protein ranging from 4 to 40 g/d (M=19; SE=2).Compared to a standard diet, DIY fortification seems to be a valuable strategy for increasing energy and protein intake in older people. However, no strong evidence was observed on the nutritional status. Implication for future. Further acceptability studies are crucial to ensure that DIY fortified foods are palatable and thus have a significant impact on the nutritional status. In addition, it would be useful for studies to better describe DIY recipes. This information would result in a better understanding of the factors that maximize the impact of DIY fortification on nutritional outcomes. Study registration: PROSPERO no. CRD42021244689.